Experimental study of cross phase influence on Reynolds stress in the HL-2A tokamak. (21st December 2017) - Guo, D.; Nie, L.; Ke, R.; Xu, M.; Wang, Z.H.; Long, T.; Wu, Y.F.; Yuan, B.D.; Gong, S.B.; Liu, H.
Abstract: The cross phase between radial velocity perturbation v ~ r and poloidal velocity perturbation v ~ θ plays an important role in the radial distribution of Reynolds stress. Recently, a novel theory of cross-phase dynamics predicts that, depending on the strength of the E   ×   B shearing, the cross phase can stay in two different states: phase locked state(weak shear regime) and phase slipping state(strong shear regime). For the first time we divided Reynolds stress into three parts, turbulence fluctuation, cross phase and coherence between v ~ r and v ~ θ, and studied their relative influences on Reynolds stress in different regimes. The profile of Reynolds stress and its three parts are measured separately by using multi-tipped Langmuir probe array. We observe that the three parts contribute to the radial distribution of Reynolds stress differently. In strong shear layer, the cross phase is randomly scattered across the layer—a signature of incoherent phase slips. Correspondingly, the radial distribution of the Reynolds stress is determined by the cross phase dynamics. In the weak shear region, the cross phase tends to stay in a coherent state (i.e. the phase locked state), where the turbulence fluctuation and coherence play a more important role. Besides, a direct relation between the coherence and the cross phase scattering is observed. Once the scattering of the cross phase increases, the coherence decreases.